Improving the Eight Graders' Reading Comprehension Comprehension through Jigsaw Technique at SMP 1 PSKD - Fransiska, Adelina (JET (Journal of English Teaching), 2017)
AbstractThe main objective of this research is to improve the eighth graders’ reading comprehension through Jigsaw technique at SMP 1 PSKD. This research is a classroom action research in two cycles. The research was done on April 12th, 2016 until May 24th, 2016. The subject of the research was the students of VIII class at SMP 1 PSKD. There were 27 students (13 males and 14 females). The instruments of the test are pre-test and post-test. The non instruments test are observation sheets, interview, and researcher’s diary notes. The improvement of the eighth graders’ reading comprehension scores can be seen from the result of the pre-test and post-test. The average score of the students in the pre-test was 49.03 points and in cycle 1 the average score of the students was 65.78 points. So the increase between the two tests was 16.75 or 34.16%. In the cycle 2, the average of students’ score was 75.85 points. The result of the posttest 1 was 65.78 points, so the increase from post-test 1 in cycle 1 to post-test 2 in cycle 2 was 10.07 points or 15.75%. The improvement from pre-test to post-test 2 was 54.70%. In addition to the score increase, jigsaw technique can improve the students’ enthusiasm in learning reading comprehension. It can be seen from the result of the interview. The participants were interested in learning reading comprehension through jigsaw technique because jigsaw technique helped them in comprehending the text. This research was also supported by the result of researcher’s diary notes. The researcher’s diary notes shows that there were a positive changed from cycle 1 to cycle 2. Based on the results of the research, it can be concluded that jigsaw technique could improve the eighth graders’ reading comprehension at SMP 1 PSKD. Keywords: jigsaw technique, reading comprehension